Consumer Brand Awareness in Using Instagram as A Brand Communication Media (Study On Instagram Account @Pasar.Idmalang) - Awaliah*, Nurul Rizki; Zuhri, Saifuddin (Riwayat: Educational Journal of History and Humanities, 2023)
Pasar.Id Malang is an e-commerce that encourages traditional market businesses to adapt digital systems and virtual buying and selling activities through an online platform, namely the Pasar.Id website. To introduce to the public, Pasar.Id Malang uses Instagram as a branding medium. However, when compared to several e-commerce Instagram accounts that also focus on selling consumer goods, small and medium enterprise (MSME) products, and basic necessities, Pasar.Id Malang still has a relatively small number of followers. This research method is qualitative with a virtual ethnography approach with the aim of uncovering and describing all subject interactions in the virtual world in this case branding activities carried out by Pasar.Id Malang through Instagram social media. Data is collected through virtual observation activities and also in-depth interviews to test the validity of the data. From the results of the study, the social media strategy that @pasar.idmalang in conducting branding to build brand awareness is an audit or discovery, determining plans in using Instagram, optimizing Instagram content, and evaluating the use of Instagram. In addition, it was found that the brand awareness of followers of Instagram @pasar.idmalang is at the supported awareness level which shows that consumers only know or remember Pasar.Id Malang when other people mention the brand.